2016
DOI: 10.1007/s00436-016-5222-z
|View full text |Cite
|
Sign up to set email alerts
|

Austrodiplostomum sp., Bolbophorus sp. (Digenea: Diplostomidae), and Clinostomum marginatum (Digenea: Clinostomidae) metacercariae in inland silverside Menidia beryllina from catfish aquaculture ponds, with notes on the infectivity of Austrodiplostomum sp. cercariae in channel catfish Ictalurus punctatus

Abstract: In the southeastern USA, catfish aquaculture is burdened by predation from piscivorous birds and the digenetic trematodes they carry. In addition to cultured ictalurid fish, other forage or incidental fish species inhabit catfish production ponds. Of these, the inland silverside Menidia beryllina was recently found to harbor larval metacercariae of several trematode species. Three species of metacercariae were reported, two of which represent the first morphological descriptions of an Austrodiplostomum sp. and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Clinostomid cercariae collected from infected snails were pooled into a 500-ml beaker, the water was gently agitated with a magnetic stir bar, and the average number of cercariae per milliliter was determined from ten 0.1 ml aliquots according to previously established protocols (Griffin et al, 2012(Griffin et al, , 2014Rosser et al, 2016b;Alberson et al, 2017). Channel catfish fingerlings (c.2-4 cm) reared indoors for infectious disease research at the Thad Cochran National Warmwater Aquaculture Center in Stoneville, MS, were used in infectivity studies.…”
Section: Fish Experimental Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinostomid cercariae collected from infected snails were pooled into a 500-ml beaker, the water was gently agitated with a magnetic stir bar, and the average number of cercariae per milliliter was determined from ten 0.1 ml aliquots according to previously established protocols (Griffin et al, 2012(Griffin et al, , 2014Rosser et al, 2016b;Alberson et al, 2017). Channel catfish fingerlings (c.2-4 cm) reared indoors for infectious disease research at the Thad Cochran National Warmwater Aquaculture Center in Stoneville, MS, were used in infectivity studies.…”
Section: Fish Experimental Challengesmentioning
confidence: 99%
“…For all cercariae and metacercariae gDNA extracts, three regions were amplified as described previously using the BD1/BD2 primers for the ribosomal ITS regions, cox1_schist5'/acox650r primers for the cox1 gene, and NDJ11/NDJ2a primers for the nad1 gene. Additionally, the nad1 gene was amplified from archived gDNA of an adult of Clinostomum marginatum from a great egret (n = 1) , metacercaria of C. marginatum from an inland silverside (n = 1) (Rosser et al, 2016b), and an adult of Clinostomum album collected from a great egret (n = 1) .…”
Section: Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although classical studies contend that species identity varies as a function of intermediate host identity (amphibians vs fishes), our findings indicated that C. marginatum often infects amphibians as well as fishes in the same habitats. Prior to recent molecular studies (Caffara et al , 2011; Sereno-Uribe et al , 2013, 2018; Pérez Ponce de León et al , 2016; Rosser et al , 2016, 2017), Clinostomum species determination was often based on geographical location (New vs Old World) and intermediate host identity (fishes vs amphibians) (Yamaguti, 1933; Hunter and Hunter, 1935; McAllister, 1990). Alongside the findings of Bonnet et al (2011), our results indicate that C. marginatum frequently infects both amphibians and fishes that co-occur in the same aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The high densities of fish present in catfish ponds have provided ideal foraging grounds for piscivorous birds, such as the American white pelican Pelecanus erythrorhynchos , great blue heron Ardea herodias , great egret Ardea alba , and double‐crested cormorant Phalacrocorax auritus . The presence of these birds has led to massive depredation and optimal conditions for propagation of trematode life cycles (Levy et al 2002; Glahn and King 2004; Yost et al 2009; Griffin et al 2012; Rosser et al 2016b, 2016c; Alberson et al 2017).…”
mentioning
confidence: 99%